2017
DOI: 10.1136/archdischild-2016-312492
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of enteral syringes with commonly prescribed paediatric liquid medicines

Abstract: To investigate the paediatric volumetric accuracy for two enteral syringe brands, using commercially available liquid drug formulations, across a range of clinically relevant volumes and physicochemical properties. Method:In vitro experiment under laboratory conditions. Ten drug formulations were tested for two syringe brands (Baxa, Medicina) using a range of formulation volumes (0.05 to 5 mL) and syringe sizes (1 to 5 mL). The weight of syringes, empty, filled and after expelling liquids were accurately measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…Healthcare professional perspectives Some of the challenges faced when administering oral liquid medicines to children with enteral syringes have been illustrated through recent research [16]. In this study, a comparison of generic oral dosing syringe brands indicated differences in dosing accuracy across brands and size of syringes, and those with a wide tip (female design) showed a greater dead space volume compared to those with a narrow tip (male design) across each syringe size (Figure 1).…”
Section: Presentationsmentioning
confidence: 74%
See 1 more Smart Citation
“…Healthcare professional perspectives Some of the challenges faced when administering oral liquid medicines to children with enteral syringes have been illustrated through recent research [16]. In this study, a comparison of generic oral dosing syringe brands indicated differences in dosing accuracy across brands and size of syringes, and those with a wide tip (female design) showed a greater dead space volume compared to those with a narrow tip (male design) across each syringe size (Figure 1).…”
Section: Presentationsmentioning
confidence: 74%
“…Oral dosing syringes are considered to be more accurate for delivering small liquid volumes compared to other oral dosing devices [10,11,18,24]. As discussed during the workshop, syringe size and design as well as the physical properties of the oral liquid itself may have an impact on dosing accuracy [16]. Indeed, correct oral (into the mouth) dosing using enteral syringes (female tips) can be challenging and prone to error, especially when the design of the drug product bottle is such that additional accessories such as a bottle adaptor and/or medicine straw are required.…”
Section: Discussionmentioning
confidence: 99%
“…Different syringes have different graduation markings. DV accuracy depends on the graduation markings and measurement volume . Parameters were calculated (Box 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…Measuring calculated doses precisely from liquid formulations can be difficult. Recommended devices, for example oral syringes, may not measure sufficiently accurately, especially when small volumes of liquids are needed …”
Section: Introductionmentioning
confidence: 99%
“…The drug efficacy and effectiveness depend on the administration of the correct dose. Thereby, the safe and effective use of antibiotics in liquid oral suspension includes the correct reconstitution, concentration, 'shake before use' procedure, dose measurement, duration of treatment, and storage conditions [6,7].…”
Section: Introductionmentioning
confidence: 99%